EKSISTENSI INDIVIDU PEKERJA SEKS KOMERSIAL DALAM KEHIDUPAN BERMASYARAKAT - Hardiyanto Hardiyanto (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study discusses positive perceptions and negative perceptions of acts of law that apply in the sintai localization of the city of Batam. The method used in this research is descriptive method by obtaining qualitative. The informants in this study were translated 14, which consisted of 5 commercial sex workers (CSWs), 2 members of the localization namely the chairman of the localization and pimps, 7 communities ,. Data collection techniques used interviews, documentation and observation. Analysis of the data used reduction, data presentation, verification, and drawing conclusions. Results obtained There are positive perceptions, i.e. (1) Accepting the location of the city of Batam, (2) negative perceptions, including people who pout and harass them by saying that they make money easily, work well, and work only with their brains (3 ) The efforts made by CSWs in the Sintai localization, namely making good relations with the surrounding community. They do anything that makes the community accept their visit. Community perception, Social Contact, and Social Communication of CSWs with the community, CSWs with fellow CSWs, CSWs with caregivers, and caregivers with the community, all went well there were no conflicts, disputes, this is in accordance with Social Relations and differences that occur in CSWs with communities in the area of the Sintai City of Batam. Relationship between CSWs communication with the community, between each of them among mutual respect, mutual support, and mutual help between each other and besides that CSWs are also comfortable living in the Sintai localization area of Batam.